2017
DOI: 10.1177/0340035216678239
|View full text |Cite
|
Sign up to set email alerts
|

Team-based data management instruction at small liberal arts colleges

Abstract: This paper describes a collaborative approach taken by librarians at five small, regional liberal arts colleges to developing/enhancing research data management services on their campuses. The five colleges collectively belong to a consortium known as the Northwest Five Consortium. Over 10 months, librarians from the five schools collaborated to plan a data management and curation workshop with the goals of developing relationships with researchers working with data, developing their own research data manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Teaching research data management to graduate students is a trend within information literacy instruction (Carlson et al 2011;Qin and D'ignazio 2010;Whitmire 2015). A variety of pedagogies have been used, including one shot guest lectures (Westra and Walton 2015), online courses (Johnston and Jeffryes 2014b), traditional courses (Bracke and Fosmire 2015), workshops (Adamick, Reznik-Zellen, and Sheridan 2012), team-based active learning (Clement et al 2017), and blended learning (Zhang, Goodman, and Xie 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Teaching research data management to graduate students is a trend within information literacy instruction (Carlson et al 2011;Qin and D'ignazio 2010;Whitmire 2015). A variety of pedagogies have been used, including one shot guest lectures (Westra and Walton 2015), online courses (Johnston and Jeffryes 2014b), traditional courses (Bracke and Fosmire 2015), workshops (Adamick, Reznik-Zellen, and Sheridan 2012), team-based active learning (Clement et al 2017), and blended learning (Zhang, Goodman, and Xie 2015).…”
Section: Introductionmentioning
confidence: 99%
“…16 Further, Clement et al note that liberal arts colleges may privilege funding toward curricular and teaching needs as opposed to research infrastructure, further limiting the resources available to the faculty. 17 One potential solution for the infrastructure disparity has been identified in a recent National Science Foundation report, which calls for dedicated funding to provide sustained midscale research infrastructure development and maintenance support. 18 Other possibilities may involve collaboration between institutions to pool resources as proposed by the Data Curation Network 19 or expanded support for disciplinary repositories and aggregators like DataONE.…”
Section: Figurementioning
confidence: 99%
“…RDM courses cover a range of topics: definitions of data and RDM; funding agency requirements and mandates; sharing and archiving data; copyright and ownership; metadata; and the reuse of shared data (Clement, Blau, Abbaspour, & Gandour-Rood, 2017;Furukawa, Ojiro, & Yamaji, 2018;Rice, 2014;Southall & Scutt, 2017). Individual courses often only cover a subset of these broad categories.…”
Section: Rdm Teachingmentioning
confidence: 99%
“…PGR students form another significant cohort. A programme training teams of support staff, students and researchers found that teaching RDM to these groups together was particularly successful (Clement et al, 2017), as was the imbedding of librarians into research groups to identify specific needs and provide training in-situ (Lyon, 2016).…”
Section: Rdm Teachingmentioning
confidence: 99%
See 1 more Smart Citation